An accumulation of climatic stress events has led to years of reduced growth for sugar maple in southern Quebec, Canada. Issue 7 (16th July 2020) - Moreau, Guillaume; Achim, Alexis; Pothier, David
Abstract: Understanding the influence of climatic variation on forest dynamics is of great ecological and economic interest, and is essential to prescribe silvicultural interventions that will facilitate ecosystem acclimation to global change. However, the retrospective identification of climatic events responsible for the inter‐annual variation of tree growth is challenging, notably because both their duration and their subsequent effects can be highly variable in time. In this study, we aimed to (1) quantify empirically the effect of climatic stress events on the short‐ and long‐term growth dynamics of sugar maple trees; (2) compare the effects of different types of climatic events, that is, drought and thaw–freeze; and (3) compare the effects of climatic stress events to those of traditional monthly level climate metrics. To achieve this, we paired cross‐dated tree‐ring series to monthly and daily‐level climate metrics over more than 50 yr in two distinct regions of southern Quebec. While the analysis from monthly level metrics first suggested a weak and non‐stationary relationship between climatic conditions and tree growth, the analysis from daily‐level metrics showed that climatic stress events, and more particularly thaw–freeze events, were strongly related to the growth of sugar maple trees. Our results suggest that the synergic influence of cumulative climatic stress events, which was exacerbated by insect outbreaks during the early 1980s, induced an important shift in the growth dynamics of sugar maple and in its response to variation in climatic conditions. These results highlight the potential negative impact of global climate change on our capacity to predict stand productivity accurately, especially if climate‐sensitive growth models are based on projections of future monthly metrics. Because adverse climatic events are expected to increase both in frequency and in severity over the next decades, a general decrease in the growth rate of sugar maple is apprehended in southern Quebec.